Improving Critical Thinking Skills of Physics Teacher Prospectives Through Case Based Learning Models - Busyairi, Ahmad; Hikmawati, Hikmawati (Jurnal Ilmiah Profesi Pendidikan, 2024)
In the complex information era, critical thinking skills become very important for educators to be able to analyze and solve problems effectively. This research aims to improve the critical thinking skills of prospective physics teachers through the application of the Case Based Learning (CBL) model. The CBL model is implemented by exposing students to realistic and relevant case studies, which encourage them to carry out in-depth analysis of limited information. This research is Action Research. The research subjects consisted of 29 prospective physics teacher students who were taking professional education courses. The results of the research show that there has been an increase in students' critical thinking skills, with the average score in cycle 1 being 80.04 to 88.792 in cycle 2. This increase reflects students' ability to provide basic explanations, and further explanations, make conclusions, and plan appropriate actions. The more effective it is based on the problem analysis that has been carried out the better. These findings confirm that the CBL model is empirically proven to be used to improve students' critical thinking skills.